Alternative news and misinterpretations: fake news and its spread in Nigeria (2020)
Down the ages and across cultures, information has occupied a very crucial space in the life of any society. Today, our world with the speed in technological advancements is characterised with easy access to the collecting, refining and distribution of information. This has left media houses especially the large ones with the burden of competing with alternative media, as media producers abuse the privilege in liberal democracies that is granted citizens as regards human rights and freedom, as the rate of disseminating false information continues to grow. This piece attempts at stating clearly information on fake news, misinformation and hate speeches as disseminated globally in the guise of media scientists, showing the means through which this end is met, especially with the easy that comes with the use of social media and in the end, showing the challenges and risks that are resultant effects of this acts.